The Role of Technological Innovation on the Effect of International Strategic Alliances on Corporate Competitiveness in Jordanian International Business Administration: Moderating and Mediating Analysis - Alkhawaldeh, Bashar Younis; Alhawamdeh, Hamzeh; Al_Shukri, Kadri S.; Yousef, Maria; Shehadeh, Abdallah Yousef Ata; Abu-Samaha, Ala M.; Alwreikat, Ahmad A.M. (Migration Letters, 2023)
Within the context of Jordanian international business management, the current study explores the subtle relationships between global strategic alliances (ISA), corporate competitiveness (CC), and technological innovation (TI). Partial Least Squares Structural Equation Modeling (PLS-SEM) is used to assess the interaction between these variables as well as the mediation and moderation effects. Utilizing a sample size of 350 individuals who occupy professional, management, and decision-making roles in Jordanian businesses engaged in international commerce, the research article shows notable and significant positive associations. The results of the path analysis show a strong relationship between global strategic alliances (ISA) and both corporate competitiveness (CC) and technological innovation (TI). This shows that ISA is essential in fostering innovation inside organizations and developing competitive strategies. Additionally, this study looks at the connection between corporate competitiveness (CC) and technical innovation (TI), finding a very strong one. This emphasizes how important technological advancement is in enhancing a company’s ability to compete. The model’s mediating and moderating effects are the focus of the study’s most important findings. The results provide solid support for the mediating role, indicating that the correlations between ISA, TI, and CC are interrelated and have an impact on one another. Furthermore, the findings of this study demonstrate a noteworthy moderation effect, suggesting the existence of external factors that exert an influence on the associations between these variables. This research provides valuable perspectives on the intricacies of global strategic partnerships, technical advancements, and corporate competitiveness within the realm of international business administration in Jordan. Through the elucidation of the complex interconnections and fundamental mechanisms, this research endeavour enhances our understanding of the influence of these factors on the competitive strategies and innovation endeavours of organisations.